THE IMPACT OF HUMAN RESOURCE COMPETENCE AND HOSPITAL MANAGEMENT INFORMATION SYSTEM (SIMRS) QUALITY ON THE EFFECTIVENESS OF ADMINISTRATIVE SERVICES AT MM INDRAMAYU HOSPITAL - Agis Gisna Wahyuni; Yoki Oktorian Sukardi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Hospital digital transformation requires human resource readiness and the quality of the Hospital Management Information System (SIMRS) for effective administrative services. In practice, the effectiveness of administrative services is still influenced by variations in employee competency and the quality of the system used. This study aims to analyze the influence of HR competency and SIMRS quality on the effectiveness of administrative services at MM Indramayu Hospital. This study uses a quantitative approach with a survey method. The study population included all non-medical support staff who use SIMRS, totaling 84 respondents, so a saturated sampling technique was used. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression with the help of SPSS. The analysis results show that HR competency has a positive and significant effect on the effectiveness of administrative services (t = 7.075; p < 0.05). SIMRS quality also has a positive and significant effect on the effectiveness of administrative services (t = 6.781; p < 0.05). Simultaneously, human resource competency and the quality of the Hospital Management Information System (MISRS) had a positive and significant effect on the effectiveness of administrative services (F = 28.257; p < 0.05) with a coefficient of determination (R²) of 0.411. This study concludes that improving the effectiveness of hospital administrative services requires synergy between adequate human resource competency and good quality of the SIMRS. Future research is recommended to examine other factors beyond the research model to gain a more comprehensive understanding